Pengaruh Penggunaan Media Sosial Instagram terhadap Pemenuhkan Kebutuhan Informasi - Awindya Wulandari; Aqida Nuril Salma (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
Abstract The use of social media, especially Instagram, is currently the focus of the Indonesian government to be used to fulfill information needs, almost all local governments use social media to communicate with the community. This is also accompanied by the use of the internet and the use of social media which is constantly increasing in Indonesia. This study was conducted to determine the effect of the use of social media Instagram @halobandung on meeting the information needs of the people of Bandung. Researchers used a quantitative research methodology by distributing online questionnaires via Google Form which were then distributed to 100 respondents via WhatsApp, LINE, and Instagram DMs. The population in this study is the people of Bandung City who know the Instagram account @halobandung. The data analysis techniques used in this study were descriptive analysis, MSI test, normality test, correlation test, coefficient of determination test, simple regression test, and the t & f hypothesis test. Based on the results of hypothesis testing using the T test and F test, the results show that there is an influence on the use of Instagram @halobandung social media on meeting the information needs of the people of Bandung City. This is evidenced by the results of the T test calculation, it is found that t_count is 7,879 greater than t_table is 1,984. it can be interpreted that H_0 is rejected and H_1 is accepted. Based on the results of these calculations, it can be interpreted that there is an influence on the use of social media Instagram @halobandung on meeting the information needs of the people of Bandung City. Keywords: @halobandung, Government, Information, Instagram, Social Media, Society